Rhombohedral Multilayer Graphene: A Magneto-Raman Scattering Study - Henni, Younes; Ojeda Collado, Hector Pablo; Nogajewski, Karol; Molas, Maciej R; Usaj, Gonzalo; Balseiro, Carlos A; Orlita, Milan; Potemski, Marek; Faugeras, Clement (Nano letters, 2016)
Graphene layers are known to stack in two stable configurations, namely, ABA or ABC stacking, with drastically distinct electronic properties. Unlike the ABA stacking, little has been done to experimentally investigate the electronic properties of ABC graphene multilayers. Here, we report on the first magneto optical study of a large ABC domain in a graphene multilayer flake, with ABC sequences exceeding 17 graphene sheets. ABC-stacked multilayers can be fingerprinted with a characteristic electronic Raman scattering response, which persists even at room temperatures. Tracing the magnetic field evolution of the inter Landau level excitations from this domain gives strong evidence for the existence of a dispersionless electronic band near the Fermi level, characteristic of such stacking. Our findings present a simple yet powerful approach to probe ABC stacking in graphene multilayer flakes, where this highly degenerated band appears as an appealing candidate to host strongly correlated states.